2010
DOI: 10.1175/2009jcli3042.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Atlantic Meridional Overturning Circulation Changes on Tropical Atlantic Sea Surface Temperature Variability: A 2½-Layer Reduced-Gravity Ocean Model Study

Abstract: Previous coupled climate model simulations reveal that a dipole-like SST pattern with cooler (warmer) temperature over the north (south) tropical Atlantic emerges in response to a slowdown of the Atlantic meridional overturning circulation (AMOC). Using a 2½-layer reduced-gravity ocean model, a systematic investigation into oceanic processes controlling the tropical Atlantic sea surface temperature (SST) response to AMOC changes by varying the strength of northward mass transport at the open boundaries was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…For example, Zhang et al (2011) show an apparent correlation between the NBC transport time series and the formation of Labrador Sea Water. Further support for this connection comes from model studies, where significant correlations exist between the AMOC strength and the NBC transport (Wen et al, 2010;Rühs et al, 2015). Rühs et al (2015) show that buoyancy-induced changes in the AMOC manifest themselves in the NBC, but that the variations are masked by strong interannual to decadal wind-driven gyre variability of the NBC.…”
Section: Introductionmentioning
confidence: 98%
“…For example, Zhang et al (2011) show an apparent correlation between the NBC transport time series and the formation of Labrador Sea Water. Further support for this connection comes from model studies, where significant correlations exist between the AMOC strength and the NBC transport (Wen et al, 2010;Rühs et al, 2015). Rühs et al (2015) show that buoyancy-induced changes in the AMOC manifest themselves in the NBC, but that the variations are masked by strong interannual to decadal wind-driven gyre variability of the NBC.…”
Section: Introductionmentioning
confidence: 98%
“…Simulation of a disruption of the AMOC by imposing massive fresh water over the North Atlantic, experiment referred to as "water hosing", produces a negative AMO-like signal. The adjustment of the system to the equilibrium state occurs, at least, in two states: a fast atmospheric adjustment from the North Atlantic SST anomalies, which includes a change in the North Pacific via anomalous westerly winds (Dong and Sutton, 2002a;Wu et al, 2008;Chiang et al, 2008) and a slow oceanic adjustment, which seems to be the responsible for the major warming over the equatorial and South Tropical Atlantic (Chang et al, 2008;Wu et al, 2008;Wen et al, 2010) tightly related to the anomalous northward return flow over the western boundary (reverse of the North Brazil Current, NBC) which permits the penetration of the subsurface warming over the north tropical Atlantic into the equatorial thermocline (Jochum and Malanotte-Rizzoli, 2001;Hazeleger and Drijfhout, 2006;Chang et al, 2008;Wen et al, 2010). Besides, similar to the SST anomalies over the extratropics, the dipolar SST over the Atlantic is explained in part by Wind-Evaporation-SST feedback (WES; Chang et al, 1997), intensifying the anomalous northeasterly winds and its thermodynamic interaction within the oceanic mixed layer (Chiang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the proximity of core locations, some proxy reconstructions record a surface cooling, while others indicate a warming. Our studies (Wan et al, 2009) (Wen et al, 2010a). We found that the North Brazil Current (NBC) reverses its direction in response to a shutdown of the AMOC.…”
Section: A) Hierarchical Modeling Of Past Climate Changementioning
confidence: 73%